Konsep Kepemilikan dalam Fiqh Muamalah: Studi Perbandingan antara Kapitalisme dan Syariah - Wardani, Arsyaferra Kusuma (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This article aims to examine the concept of ownership in Islamic jurisprudence of muamalah and compare it with the view of the capitalist economic system. The research approach uses a literature study with content analysis on the thought of Taqiyuddin An-Nabhani and scholars of Islamic economics. In the system of capitalism, individual ownership is absolute in nature and virtually without limits, while in the Islamic economy, ownership is derived from the provisions of the Shariah with a division of types: individual, public, and state. The article concludes that the Islamic system strikes a balance between individual property rights and social responsibilities, as well as keeping the distribution of wealth from accumulating on a handful of people.